Legitimacy and Criminal Justice: The Benefits of Self-Regulation - Tyler, Tom R. (2009)
In this lecture I argue for the value of a self-regulatory approach to law and criminal justice. I do so by first describing and critiquing the dominant approachto regulation in use today: deterrence. I suggest that in practice this model is costly and minimally effective in securing compliance with the law and motivating the acceptance of decisions made by police officers and judges. I then outline a different, self- regulatory model which focuses on engaging people's values as a basis for motivating voluntary deference to the law. I review empirical research suggesting that this strategy is both viable and more desirable than current sanction-based approaches. My argument is that this approach is particularly important when the goal is voluntary compliance with the law and/or willing cooperation with legal authorities